A multi-redox responsive cyanometalate-based metallogel - Mitsumoto, Kiyotaka; Cameron, Jamie; Wei, Rong Jia; Nishikawa, Hiroyuki; Shiga, Takuya; Nihei, Masayuki; Newton, Graham; Oshio, Hiroki (Wiley-VCH Verlag, 2017)
A tetrathiafulvalene (TTF) based tridentate ligand (-(4’-methyl-4,5-di-n-dodecylthylthiotetrathiafulvalene-5’-ylthio)-’-[tris-2,2,2-(1-pyrazolyl)ethoxy]-p-xylene) (L) with long-chain alkyl moieties was prepared in order to obtain a new multi-redox active gelator based on a mixed-metal octanuclear complex [FeIII4NiII4(CN)12(tp)4(L)4](BF4)4 (1). The magnetism, electrochemistry and gelation behaviour of 1 were studied and 1,2-dichlorobenzene solutions of 1 are shown to display thermoreversible gelation behaviour at room temperature. Furthermore, the gel phase of 1 is shown to undergo room-temperature gel-to-sol transformations induced by both the oxidation and reduction of the gelator complex by F4TCNQ or [FeII(Cp*)2], respectively.